EFEK RELAKSASI OTOT PROGRESIF DISERTAI MUSIK KLASIK TERHADAP STRESS DAN TEKANAN DARAH PASIEN HIPERTENSI SECARA CEPAT - Gultom, Agustina Boru; Batubara, Arbani; Afniwati, Afniwati (Universitas Mataram, 2024)
The Sunggal Community Health Center is in Sunggal District, Medan City, and has several health problems. Hypertension is ranked third among the ten most common diseases in 2022. One of the work areas of the Sunggal Health Center in Medan City where there are many hypertensive patients is the Sunggal sub-district area, with hypertension patients. some experienced an increase in their blood pressure, some experienced an increase in tension in daily life. The aim of this activity is that people who experience hypertension will experience a decrease in stress and blood pressure through progressive muscle relaxation exercises accompanied by classical music. . Community service activities include measuring stress using the SUDS (Subjective Units of Distress Scale) questionnaire and blood pressure using an Omron brand digital blood pressure monitor before training begins. Then the intervention continued in the form of progressive muscle relaxation exercises accompanied by classical music using lecture, question and answer, demonstration and re-demonstration methods for progressive muscle relaxation exercises accompanied by classical music. Then, measure stress and blood pressure again using the same questionnaire and tools. The target was 30 hypertensive patients carried out in the Sunggal sub-district. The results of the activity showed a decrease in stress by 23.68%, a decrease in systolic blood pressure by 9.47 mmHg, diastolic by 4.00 mmHg. Progressive muscle relaxation exercises accompanied by classical music can make a good contribution as a non-pharmacological nursing intervention in reducing stress and lowering blood pressure in hypertensive patients quickly.